ANALISIS TINGKAT PARTISIPASI ANGGOTA KELOMPOK TANI DALAM PENERAPAN SISTEM TANAM JAJAR LEGOWO PADI SAWAH (oriza sativa L) - Sefridanti, Iga; Hendrita, Vivi (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2024)
AbstractThe government has carried out an increase in rice production and productivity through the Agricultural Extension Agency (BPP) by implementing the Jajar Legowo planting program. To get good results, farmer participation is very necessary in its implementation. This research aims to: (1) Find out the level of farmer participation in implementing Jajar Legowo planting (2) Find out the obstacles in implementing Jajar Legowo planting. The sampling technique uses the proportional random sampling method using the Slovin formula. Data analysis in this research used scoring methods and structured interviews. The results of this research show that (1) The level of participation of farmer group members in implementing the Jajar Legowo planting system has 4 stages, namely: The level of participation in the planning stage is included in the active category with a percentage of 73.66%. The level of participation in the implementation stage is included in the active category with a percentage of 66. .58%, the utilization stage participation rate is included in the active category with a percentage of 71.54%, and the evaluation stage participation rate is included in the active category with a percentage of 69.42%. (2) The obstacles experienced by farmers in implementing jajar legowo planting include 4 aspects, namely: (1) Technical aspects (2) Capital (3) Internal farmers.Keywords: Farmer Group, Jajar Legowo, Participation, Paddy Field